2018
DOI: 10.32601/ejal.464179
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Factors in Multilingual Students' Learning Additional Languages: The Case of English and Turkish

Abstract: APA Citation: Dincer, A. (2018). Motivational factors in multilingual students' learning additional languages: The case of English and Turkish. AbstractThe current study examined the relationships among motivational factors (i.e., motivation types and motivational strength, and language anxiety) in the simultaneous learning process of additional languages. A mixed-methods design was conducted with 86 multilingual learners learning both English and Turkish. The data were collected using a survey and follow-up o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Azar & Tanggaraju (2020) conducted their study on motivation in second language acquisition in Malaysia. Dincer (2018) researched motivational factors in additional language learning in Turkey and used a questionnaire with 26 items. Choomthong & Chaichompoo (2015) conducted their research on students' motivation to learn English, they used a questionnaire with 14 items.…”
Section: Motivation Studies and Their Instrumentsmentioning
confidence: 99%
“…Azar & Tanggaraju (2020) conducted their study on motivation in second language acquisition in Malaysia. Dincer (2018) researched motivational factors in additional language learning in Turkey and used a questionnaire with 26 items. Choomthong & Chaichompoo (2015) conducted their research on students' motivation to learn English, they used a questionnaire with 14 items.…”
Section: Motivation Studies and Their Instrumentsmentioning
confidence: 99%
“…People, specifically L2 learners may have missed many opportunities in the study or life as the world now necessitates for English interaction for varied transactions. However, it is learnt that with the students' intrinsic motivation to learn English -knowing that English is greatly used worldwide for business and international transactions; for both written and oral communication -it is found that this group has the potential to excel in learning English language (Dincer, 2018). Anyhow, one of the reasons related to the unwillingness to speak up especially when using English language could be the individual's speaking anxiety (Shirkhani, et al 2020); in which people are found to feel exceptionally comfortable when relying on a written script when they speak or present as they can avoid themselves from being nervous when speaking (Wilang, 2018).…”
Section: Second Language Learners' Anxiety To Speaking English -The Cause and Effectmentioning
confidence: 99%
“…Moreover, the motivational development might not be the same for all students. Previous studies indicate systematic individual differences in students’ motivational beliefs depending, for instance, on their gender, language background (Brühwiler & Le Pape Racine, 2017; Rjosk et al., 2015; Walter & Taskinen, 2008), or experience with learning several languages at home (Dincer, 2018; Lanvers et al., 2019; Thompson & Lee, 2018).…”
mentioning
confidence: 99%